Announcement of COVID-19 cases in Indonesia on the Indonesian Stock Market: Analysis of a Study of Events in Miscellaneous Industry - Miharja, Rifki Andi; Widajatun, Vincentia Wahju (Technium Social Sciences Journal, 2021)
The first Covid-19 case was announced on March 2, 2020. This study aims to determine whether there is a difference between the abnormal return before the announcement and after the announcement of the first Covid-19 case in Indonesia (case Study of Events in Miscellaneous Industry). The research data was taken 30 days before and 30 days after the announcement of the first case of Covid-19 in Indonesia. The data were processed using SPSS. From the results of data processing, it shows that there are differences in the index prices of Miscellaneous industry before and after the announcement of the first Covid-19 case in Indonesia. This is indicated by a significant value of 0.00 <0.05.